Tantangan Pendidikan Kewarganegaraan dalam Meningkatkan Kualitas Pembelajaran - Ipah Amelia; Nida Nadifatun Nafiah; Amila Amalia Asca; Masduki Masduki (Prosiding Seminar Nasional Ilmu Pendidikan, 2026)
This study examines various challenges facing Pancasila and Citizenship Education (PPKn) in improving the quality of student learning. The study focuses on the application of technology-based learning media, students' socioeconomic status, the use of group discussion methods, and the implementation of the Independent Curriculum (Curriculum Merdeka) to improve students' civics knowledge. The study was conducted using a literature review method, examining various journals and scientific articles from the past five years. The study found that PPKn learning still faces various obstacles, such as low student motivation, limited use of engaging media, and suboptimal implementation of participatory learning. Conversely, the use of digital media and group discussion techniques is considered to increase student participation and critical thinking skills. The implementation of the Independent Curriculum also has a positive impact because it focuses more on strengthening students' character and learning experiences. Therefore, collaboration between teachers, schools, and the government is crucial for improving PPKn learning and better aligning it with students' current needs.